Improving Students’ Speaking Skill through Communicative Approach: Discussion - Mansyur, Mansyur; Syamsuddin, Muhammad Rifqi; Aeni, Nur (Journal of English Culture, Language, Literature and Education, 2024)
The research aimed to determine whether the use of a communicative approach (discussion) improves students’ speaking skills. The researcher applied a pre-experimental method with a one-group pretest-posttest design. The variables of the research were independent and dependent. The independent variable was discussion. The dependent variable was the students’ speaking skills. The population of this study was the second-grade students of MAN Baraka Kab. Enrekang in the academic year of 2023/2024. A total of 31 students in one class were decided by using the cluster random sampling technique. The data were obtained by administering the speaking test to the XI MIA 4 and analyzed by using SPSS 20 to know about the result of the student’s scores. The researcher found the results that discussion improves students’ speaking skills. The mean score of the pre-test was 25.62 with a standard deviation was 8.56 and the mean score of the post-test was 45.34 with a standard deviation was 12.26. So, it is concluded that the students of second-grade students of MAN Baraka Kab. Enrekang showed significant improvement in their speaking skills.